Pemanfaatan Aplikasi Google Form Sebagai Alat Evaluasi Pembelajaran Pendidikan Agama Islam Siswa - Pane, Mardiani; Edawarni, Cici; Asiyah, Asiyah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the responses of students and teachers of Islamic Religious Education (PAI) in using the google form as an evaluation tool for PAI learning at SMPN 23 Bengkulu Utara. The method used is qualitative with the type of research field research (field research). This research is a field study of class VIIIB students in the mid-odd semester of the 2021-2022 academic year using Google Forms as an evaluation tool for PAI learning. The data collection technique used is a questionnaire/questionnaire in the form of a google form, observation, interviews, and documentation studies. The results show that the use of google forms in PAI learning evaluation activities has an impact and benefit both from the aspects of effectiveness, efficiency, attractiveness and to the display design, although some of the weaknesses of using google forms such as higher cheating rates and the use of google forms by students are still impressed. play around. In conclusion, the use of the Google Form application for carrying out daily and semester assessments in the future can continue to be used by teachers in all subjects, because it saves time, costs and is easy and makes it easier for teachers to create online questions, save online questions, and obtain student grade data. practically and quickly. Keywords: Google form, learning evaluation, PAI